(untitled) (Amsterdam, 2006)
This book is a fundamental VLSI Testing and Design-for-Testability (DFT) textbook allowing undergraduates, DFT practitioners, and VLSI designers to learn quickly the basic VLSI Test concepts, principles, and architectures, for test and diagnosis of digital, memory, and analog/mixed-signal designs. VLSI Testing is very basic to the semiconductor industry and is something that almost everyone in the industry needs to have some knowledge of. It is often not sufficiently covered in undergraduate curricula; therefore this book fill the gap in this area for both students and professionals in semiconductor manufacturing, design, systems, electronic design automation (EDA), etc. As 100 million transistor designs are now common, test costs are 25-40% of the overall cost of manufacturing a chip and how a chip is designed greatly impacts the cost of test. As such, it is important for designers and managers to understand the concepts and principles of testing and design-for-test techniques.
Keywords: Integrated circuits,Integrated circuits,Mạch tích hợp,Mạch tích hợp; Very large scale integration,Testing,Very large scale integration,Design,Mạch tích hợp quy mô lớn,Kiểm tra,Mạch tích hợp quy mô lớn,Thiết kế